The Euler–Lagrange equation for the Anisotropic least gradient problem. (October 2016) - Mazón, José M.
Abstract: In this paper we find the Euler–Lagrange equation for the anisotropic least gradient problem inf ∫ Ω ϕ ( x, D u ) : u ∈ B V ( Ω ), u | ∂ Ω = f being ϕ a metric integrand and f ∈ L 1 ( ∂ Ω ) . We also characterize the functions of ϕ -least gradient as those whose boundary of the level set is ϕ -area minimizing in Ω .